(3Yjhf GdeYGQa hafhf CNHGQ GdNdGFas - (3eMeO Hf SdGeI Hf LYaQ Hf Ydj Hf Mcehf GdbVGYj , TgGH GdOjf CHh YHO Gddg,J (B454 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eHOF cd TF hhGQKg heejJ cd Mdj hHGYKg s
(3BNQgG (B:s
(3hBNQ eG ajgG Edi fgGjI NdGaI GdMGce HCeQ Gddg GdaGWei HeUQ ai SfI (B411(3g` s
(3Cdag ai JGQjN GdYGde efP GdNdjbI Edi SfI (B417 (3ai CjGe GdOhdI GdaGWejIs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B42 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B71s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B111 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs